MORPHOLOGICAL AND SYNTACTICAL ERRORS IN STUDENTS’ DESCRIPTIVE WRITING - Hannisa Haris; Muhammad Sulhan (INFERENCE: Journal of English Language Teaching, 2022)
This research aims to: 1) show types of morpholigical errors in descriptive writing, 2) to show types of syntactic erros in descriptive writing, 3) to show types of errors, in terms of morphology or syntact in descriptive writing. It uses qualitative method (case study). It was conducted in SMA Negeri 1 Bangkinang Kota, Riau. It has started in September to completion. The 62 sample were gained through random sampling. The error classification sheets, which are derived from 62 students’ writing from SMA Negeri 1 Bangkinang, are used for the research instrument. The results of this research are: 1) there are some morphological errors in students’ descriptive writing, such as inflection, derivation, noun, adjective, verb, adverb, preposition, article, copula (be), auxiliary, conjunction, and pronouns. The errors mostly occur in auxiliary with a percentage of 14.67%. 2) there are some syntactical errors in students’ descriptive writing, such as passive voice, tense, noun phrase, prepositional phrase, subject/predicate, subject-verb agreement, demonstrative determiner, and paired adjective. The errors highly occur in Subject-verb agreement with a percentage of 23.04%. 3) The morphological and syntactical errors occur in the ommision, addition, misformation, and misordering.